Effects of prescribed fire and post-fire rainfall on mercury mobilization and subsequent contamination assessment in a legacy mine site in Victoria, Australia. (January 2018) - Abraham, Joji; Dowling, Kim; Florentine, Singarayer
Abstract: Prescribed fire conducted in fire-prone areas is a cost-effective choice for forest management, but it also affects many of the physicochemical and bio-geological properties of the forest soil, in a similar manner to wild fires. The aim of this study is to investigate the nature of the mercury mobilization after a prescribed fire and the subsequent temporal changes in concentration. A prescribed fire was conducted in a legacy mine site in Central Victoria, Australia, in late August 2015 and soil sample collection and analyses were carried out two days before and two days after the fire, followed by collection at the end of each season and after an intense rainfall event in September 2016. Results revealed the occurrence of mercury volatilization (8.3–97%) during the fire, and the mercury concentration displayed a significant difference (p < 0.05) before and immediately after the fire. Integrated assessment with number of pollution indices has shown that the study site is extremely contaminated with mercury during all the sampling events, and this poses a serious ecological risk due to the health impacts of mercury on human and ecosystems. In times of climate fluctuation with concomitant increase in forest fire (including prescribed fire), and subsequent precipitation and runoff, the potential for an increased amount of mercury being mobilized is of heighted significance. Therefore, it is recommended that prescribed fire should be cautiously considered as a forest management strategy in any mercury affected landscapes. Graphical abstract: Image 1 Highlights: Legacy gold mining sites have elevated Hg concentration. Hg sequestered in the soil organic matter and vegetation limiting its mobility. Prescribed fires are able to release and remobilize sequestered Hg. The liberated Hg mobilized to atmosphere mostly as Hg 0 and the rest as PHg. Post-fire rainfall increased the Hg concentration in the soil.